2015
DOI: 10.1021/ci500662d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Water Molecules—A Statistical Evaluation of Water Molecules Based on Electron Density

Abstract: Water molecules play important roles in many biological processes, especially when mediating protein-ligand interactions. Dehydration and the hydrophobic effect are of central importance for estimating binding affinities. Due to the specific geometric characteristics of hydrogen bond functions of water molecules, meaning two acceptor and two donor functions in a tetrahedral arrangement, they have to be modeled accurately. Despite many attempts in the past years, accurate prediction of water molecules-structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 70 publications
0
56
0
1
Order By: Relevance
“…the real-space correlation coefficient (29) or the real-space difference density Z-score (30). Recently, we developed the electron density score for individual atoms (EDIA) (31) as a measure for estimating how well each atom position in a certain structure is supported by the experimental electron density. For all life scientists basing their research on individual structural features of a protein or a nucleic acid, it is essential to know this degree of experimental support for each atom, functional group or ligand molecule.…”
Section: The Proteinsplus Servermentioning
confidence: 99%
“…the real-space correlation coefficient (29) or the real-space difference density Z-score (30). Recently, we developed the electron density score for individual atoms (EDIA) (31) as a measure for estimating how well each atom position in a certain structure is supported by the experimental electron density. For all life scientists basing their research on individual structural features of a protein or a nucleic acid, it is essential to know this degree of experimental support for each atom, functional group or ligand molecule.…”
Section: The Proteinsplus Servermentioning
confidence: 99%
“…A recently published statistical analysis of 2.3 million water molecules found that close to 40% of captured (buried) waters with clear electron density made no hydrogen bond with a neighboring water. 70 In Figure 6, waters capable of making hydrogen bonds with two or more other crystallographic waters are plotted as squares. These tend to lie further from the regression line between SZMAP n_ddG and RETI ∆Gabs than other waters.…”
Section: Resultsmentioning
confidence: 99%
“…For our new developed cross‐mutation experiment, we compiled a new data set. The PDB structures were selected from the same data set of high‐quality crystal structures as above (criteria: high resolution (≤1.5 Å) and electron density data available) . Within this data set, we searched for pairs of homologous proteins deviating only by 1 (single) to 5 (multiple) mutations with the tool SIENA .…”
Section: Methodsmentioning
confidence: 99%